Meanings of community across medieval Eurasia - Hovden, Eirik; Lutter, Christina; Pohl, Walter (2016)
This volume explores some of the many different meanings of community across medieval Eurasia. How did the three 'universal' religions, Christianity, Islam and Buddhism, frame the emergence of various types of community under their sway? The studies assembled here in thematic clusters address the terminology of community; genealogies; urban communities; and monasteries or 'enclaves of learning': in particular in early medieval Europe, medieval South Arabia and Tibet, and late medieval Central Europe and Dalmatia. It includes work by medieval historians, social anthropologists, and Asian Studies scholars. The volume present the results of in-depth comparative research from the Visions of Community project in Vienna, and of a dialogue with guests, offering new and exciting perspectives on the emerging field of comparative medieval history.